2023
DOI: 10.3390/jpm13010140
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hyponatremia in Heart Failure: Practical Considerations

Abstract: Hyponatremia is commonly encountered in the setting of heart failure, especially in decompensated, fluid-overloaded patients. The pathophysiology of hyponatremia in patients with heart failure is complex, including numerous mechanisms: increased activity of the sympathetic nervous system and the renin–angiotensin–aldosterone system, high levels of arginine vasopressin and diuretic use. Symptoms are usually mild but hyponatremic encephalopathy can occur if there is an acute decrease in serum sodium levels. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 100 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Potassium and magnesium homeostasis also demonstrates great significance in the management of HF patients. Low potassium serum levels promote the development of hyponatremia by shifting sodium into the cell and cause higher mortality of arrhythmic death ( 47 ). Potassium disturbance is a potent predictor both in short-term and long-term mortality of HF patients ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium and magnesium homeostasis also demonstrates great significance in the management of HF patients. Low potassium serum levels promote the development of hyponatremia by shifting sodium into the cell and cause higher mortality of arrhythmic death ( 47 ). Potassium disturbance is a potent predictor both in short-term and long-term mortality of HF patients ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with persistent hyponatremia, those with more severe hyponatremia at discharge (<130 mmol/L) were proved to have higher 30day readmission or mortality, than those with less severe hyponatremia at discharge (130–134 mmol/L) ( 46 ). Moreover, for the management of the HF patient complicated hyponatremia, saline administration or fluid restriction and the use of hypertonic saline with loop diuretics are main treatments in dilutional or depletiona phenotypes of hyponatremia ( 47 ). Close monitoring and appropriate protocol of serum sodium correction are employed to avoid rapid correction, especially in severe hyponatremia (<125 mmol/L) ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies demonstrated the strong prognostic value of hyponatremia being associated with a prolonged hospital length of stay, higher risk of readmission, and in hospital and after discharge mortality [ 31 35 ]. However, there is no clear indication yet whether hyponatremia in itself influences the prognosis or whether it just occurs more often in patients with heart failure [ 36 ]. Also, concrete evidence is still in absence to demonstrate the advantage of tolvaptan [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin not only causes water retention but also results in kidney dysfunction in heart failure patients. These abnormalities are associated with the occurrence of hyponatremia, which may limit the use of several agents such as diuretics for the management of heart failure [260][261][262][263]. Nonetheless, various therapies based on the antagonist effects of different agents on both the V 1a receptor and V 2 receptors have been developed for the treatment of heart failure [197].…”
Section: Role Of Vasopressin In Cardiac Hypertrophy and Heart Failurementioning
confidence: 99%